بناء الشخصية في رواية الدار الكبيرة لمحمد ديب - فالح, بريبش, هالة كوثر (جامعة الوادي University of Eloued, 2019)
تندرج هذه الدراسة في سياق محاولة البحث عن بناء الشخصية في رواية "الدار الكبيرة" للروائي الجزائري " محمد ديب" وذلك من خلال طرحه لأحداث الواقع البشري المعاش بواسطة شخصيات من وحي الواقع، فالروائي هنا يضعنا أمام تراجيديا حقيقة في روايته، وعليه فالشخصية الروائية من العناصر الأدبية الهامة، فلا يمكن أن تبني رواية دون شخصيات. وقد حاولنا في هذا العمل الكشف عن الأبعاد الخارجية والداخلية والاجتماعية للشخصيات المتواجدة في الرواية معتمدين على المنهج البنيوي لأننا قمنا بتحليل بنية الThis study is part of the attempt to search for the construction of the character in the novel "The Grand House" of the Algerian novelist, "Mohammed Deeb", by introducing the events of human reality lived by characters inspired by reality, the novelist here puts us in front of a real tragedy in his novel, so the fictional character of the elements Literary literature, can not build a novel without characters. In this work, we tried to reveal the external, internal and social dimensions of the characters in the novel based on the structural approach because we analyzed the character structure. شخصيات.
Keywords: البناء، الشخصية، المنهج البنيوي، الدار الكبيرة; Construction, personal, structural approach, big house